Core strength and voice of popular singers: randomized clinical trial (Research, Society and Development, 2020)
Objective: to investigate the effect of intensive physical therapy training of the core strength on acoustic vocal measurements of popular singers. Methods: Fifteen popular adult professional singers, divided into a study group and a control group, performed acoustic vocal assessment before and after intensive physical therapy training at the core strength. The results were compared statistically. Results: The study group showed a significant increase in the Smoothed Amplitude Perturbation Quotientand the Amplitude Coefficient of Variation after training. Conclusion: In the group of popular adult professional singers who received intensive physical therapy training from the core strength, there was an increase in two measurements of amplitude perturbation or shimmer that indicate instability of sound pressure and irregularity of vocal amplitude cycle-by-cycle, showing that the proposed training had no positive effects on the measurements of glottal source of the singers analyzed.